2012
DOI: 10.1007/s12663-012-0435-x
|View full text |Cite
|
Sign up to set email alerts
|

Is Pederson Index a True Predictive Difficulty Index for Impacted Mandibular Third Molar Surgery? A Meta-analysis

Abstract: The aim of this meta-analysis was to find out the clinical reliability of Pederson index in assessing the difficulty of surgery for impacted mandibular 3rd molar. The relevant articles were selected by Hand search and electronic media (Medline, Pubmed, Embase Cochrane library, ISI web of science) from Jan 2000 to Dec 2010. All the relevant articles were properly screened and findings were extracted from the articles. Pederson index had shown low sensitivity and specificity in predicting the difficulty of surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 14 publications
1
33
0
4
Order By: Relevance
“…Females were reported to have more pain intensity levels postsurgically than males as well as the more the surgical difficulty the more the pain experienced. [ 5 36 37 38 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…Females were reported to have more pain intensity levels postsurgically than males as well as the more the surgical difficulty the more the pain experienced. [ 5 36 37 38 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…The Pederson index predicts surgical extraction difficulty using both Pell-Gregory classification and Winter's classification. Unlike Pell-Gregory classification, the Pederson index4 includes angulation factor, although some studies and analyses have concluded that it is not a reliable test for predicting surgical difficulty of third molar surgery and should not be employed as a sole instrument for preoperative assessment of difficulty456.…”
Section: Introductionmentioning
confidence: 99%
“…A search in the literature has shown that only few studies attempted to evaluate elements, which can complicate surgical removal of impacted mandibular third molars [1]. Among these studies, Pederson difficulty index (Table 1) which is mainly based upon anatomical and radiographic features, including angulations, depth, and ramus relationship [2].…”
Section: Introductionmentioning
confidence: 99%